Anti-c-Mpl antibodies in immune thrombocytopenia suppress thrombopoiesis and decrease response to rhTPO. Issue 170 (October 2018) - Jing, Fang-Miao; Zhang, Xiao-Lin; Meng, Fan-Li; Liu, Xiao-Ming; Shi, Yan; Qin, Ping; Wang, Lin; Zhou, Hai; Hou, Yu; Song, Qiang; Peng, Jun; Hou, Ming
Abstract: Introduction: Anti-TPO receptor (anti-c-Mpl) antibodies exist and could affect rhTPO treatment in ITP. Materials and methods: Anti-c-Mpl autoantibodies and TPO levels were measured in serum from 187 ITP patients and 59 healthy controls. The anti-c-Mpl-antibody-positive (anti-c-Mpl+) and anti-c-Mpl-antibody-negative (anti-c-Mpl−) IgG from ITP patients were assessed on megakaryocyte proliferation, polyploidy, apoptosis, and platelet release with rhTPO treatment. Results: Anti-c-Mpl antibodies were detected in 54/187 ITP patients but in none of the controls. ITP patients with anti-c-Mpl antibodies had higher serum TPO levels, but lower megakaryocyte and platelet counts compared with anti-c-Mpl− patients. Antibodies targeting platelet glycoprotein (GP) were also more frequently identified in anti-c-Mpl+ ITP patients. Moreover, patients with anti-c-Mpl antibodies were less responsive to rhTPO treatment than patients without anti-c-Mpl antibodies. Additionally, the anti-c-Mpl antibody titer decreased in ITP patients following treatment. In vitro study, lower megakaryopoiesis, platelet generation and percent of polyploidy were observed in anti-c-Mpl+ group compared with the anti-c-Mpl− group in the presence of rhTPO. Conclusions: Our findings demonstrated that the anti-c-Mpl antibody represents a novel indicator of poor prognosis and may be a potential therapeutic target in ITP. Highlights: Anti-c-Mpl antibodies were detected in ITP patients and various thrombocytopenic disorders but in none of the controls. Anti-c-Mpl+ ITP patients have decreased megakaryocytes and platelet counts and are correlated with higher TPO levels. Anti-c-Mpl antibody positivity is associated with decreased therapeutic rhTPO efficacy. Purified anti-c-Mpl IgG from ITP patients suppress megakaryocyte and platelet production in the presence of rhTPO in vitro .